2017
DOI: 10.4018/ijcallt.2017070103
|View full text |Cite
|
Sign up to set email alerts
|

Learning Language Through Facebook

Abstract: This article seeks to account for the experiences of tertiary students of German when a Facebook group and associated tasks is introduced as an assessed element of their language course. Ethnographic methods were applied, such as pre-, post questionnaires, interviews and fieldnotes. The data was collected by the instructor/researcher and subjected to thematic analysis. The students (n = 23) enjoyed Facebook but mostly used the site passively and only actively posted when required. This led to a flurry of posts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In light of the above, using social networking sites such as Facebook in educational environments to build telecollaborative communities of learners from different geographical and cultural contexts that work together to achieve a common goal comes as a natural step, following the experience gained over the last decade (Reinhardt, 2018). In fact, several studies have been conducted on the use of social networking platforms (see, e.g., Aydin, 2012;Blattner & Fiori, 2013;Godwin-Jones, 2019;Leier, 2017;Promnitz-Hayashi, 2011;Reinhardt, 2018; ) and there is now widespread consensus on their effectiveness to … empower learners to see language learning as integral to real-world experiences and also help instructors to see the bigger picture of contributing to fighting stereotypes, encouraging empathy, and working toward social justice. (...) Through social participation, individual autonomy is enhanced, language skills are developed, and personal identity is expanded.…”
Section: Integrating Technologies and Project-based Learning Into Foreign Language Teachingmentioning
confidence: 99%
“…In light of the above, using social networking sites such as Facebook in educational environments to build telecollaborative communities of learners from different geographical and cultural contexts that work together to achieve a common goal comes as a natural step, following the experience gained over the last decade (Reinhardt, 2018). In fact, several studies have been conducted on the use of social networking platforms (see, e.g., Aydin, 2012;Blattner & Fiori, 2013;Godwin-Jones, 2019;Leier, 2017;Promnitz-Hayashi, 2011;Reinhardt, 2018; ) and there is now widespread consensus on their effectiveness to … empower learners to see language learning as integral to real-world experiences and also help instructors to see the bigger picture of contributing to fighting stereotypes, encouraging empathy, and working toward social justice. (...) Through social participation, individual autonomy is enhanced, language skills are developed, and personal identity is expanded.…”
Section: Integrating Technologies and Project-based Learning Into Foreign Language Teachingmentioning
confidence: 99%
“…AfewresearchershaveusedtasksasinTBLTsituatedonFBintheirlanguageclasses (Blattner &Fiori,2011;Leier,2017;Foogooa&Ferdinand-James,2017),withoneofthefirststudiesusing itinalanguageclassandasapartoftheoverallassessmentconductedbyBlattnerandFiori(2011). SpanishlanguagelearnersintheUSaccessedFBtoobserveappropriatelanguageusage,especially greetingsinspecificcontexts.Thestudentsfoundthatunderstandingtheauthenticlanguagewas challenging,butthetaskincreasedtheirsociopragmaticawareness.BlattnerandFiorialsofocused onraisingawarenessofspeechactsonFBtotriggerfutureproduction:"Thissociopragmatictaskwas chosentodevelopcommunicativecompetence,whichwouldleadtoproduction"(p.37).Likewise, Leier(2017)integratedtasksinanFBgroupaspartoftheassessment.HerGermanlanguagestudents communicated with each other over a period of 12 weeks. The platform enhanced developing a stronger class community and cultivating writing skills in the target language, particularly when applyinginformallanguage.Moreover,FoogooaandFerdinand-James(2017)researchedEnglishas aSecondLanguage(ESL)studentengagementthroughtwoonlinecommunicationtools:alearningmanagementsystem(LMS)andanFBgroup.Indeed,thesetoolsengagedthestudents,astheyenjoyed thecombinationmorethanmerelyusinganLMS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After finding that students already use social media networks such as Facebook to converse with their classmates regarding courses and assessment (Donlan, 2014;Towner & Lego Muñoz, 2011), researchers investigated the use of Facebook for formal learning, including language learning (Annamalai, 2016;Leier, 2017;Omar, Embi, & Yunus, 2012), tourism education (Chen, 2018), and sport coaching (Donlan, 2014). They found that formally assessed Facebook activities were not well-received by students, who struggled to maintain the formal strictures of educational assessment, such as appropriate language and deadlines, on an informal platform (González-Ramírez, Gascó, & Taverner, 2015;Leier, 2017). In addition, students may not wish to engage with their lecturers on Facebook (González-Ramírez et al, 2015), or only passively interacted with the Facebook page/group in question (Chugh & Ruhi, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the use of formal assessment allows for student feedback or grade analysis from an identifiable student cohort, informal learning requires different metrics. Some studies of formal learning have used Facebook metrics to analyse student behaviour on the Facebook page, in addition to qualitative measures (Donlan, 2014;Leier, 2017). Core Facebook metrics for each post on a Facebook page include the number of likes ("comparable to a non-committal smile or a nod at something you like or that you were interested in", Mauda & Kalman, 2016, p. 3527), shares ("where the user is suggesting to his or her own circle of friends to engage with a certain message", p. 3527), and comments ("comparable to expressing an opinion about a brand or an organization, or about their message", p. 3527).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation